A cross section of autosomal recessive limb-girdle muscular dystrophies in 38 families. Issue 5 (1st May 2000) - Dinçer, Pervin; Akçören, Zuhal; Demir, Ercan; Richard, Isabelle; Sancak, Özgür; Kale, Gülsev; Özme, Sencan; Karaduman, Ayse; Tan, Ersin; Urtizberea, J Andoni; Beckmann, Jacques S; Topaloglu, Haluk
Abstract : Limb-girdle muscular dystrophies constitute a broad range of clinical and genetic entities. We have evaluated 38 autosomal recessive limb-girdle muscular dystrophy (LGMD2) families by linkage analysis for the known loci of LGMD2A-F and protein studies using immunofluorescence and western blotting of the sarcoglycan complex. One index case in each family was investigated thoroughly. The age of onset and the current ages were between 1½ and 15 years and 6 and 36 years, respectively. The classification of families was as follows: calpainopathy 7, dysferlinopathy 3, α sarcoglycan deficiency 2, β sarcoglycan deficiency 7, γ sarcoglycan deficiency 5, δ sarcoglycan deficiency 1, and merosinopathy 2. There were two families showing an Emery-Dreifuss phenotype and nine showing no linkage to the LGMD2A-F loci, and they had preserved sarcoglycans. γ sarcoglycan deficiency seems to be the most severe group as a whole, whereas dysferlinopathy is the mildest. Interfamilial variation was not uncommon. Cardiomyopathy was not present in any of the families. In sarcoglycan deficiencies, sarcoglycans other than the primary ones may also be considerably reduced; however, this may not be reflected in the phenotype. Many cases of primary γ sarcoglycan deficiency showed normal or only mildly abnormal δ sarcoglycan staining.